Histone methylation: at the crossroad between circadian rhythms in transcription and metabolism - González-Suárez, Mirna; Aguilar-Arnal, Lorena (Frontiers in Genetics, 2024)
Circadian rhythms, essential 24-hour cycles guiding biological functions, synchronize organisms with daily environmental changes. Evolutionary conserved, these rhythms govern key processes like feeding, sleep, metabolism, body temperature, and endocrine secretion. The central clock, located in the suprachiasmatic nuclei (SCN), orchestrates a hierarchical network, synchronizing subsidiary peripheral clocks. At the cellular level, circadian expression involves transcription factors and epigenetic remodelers, with environmental signals contributing flexibility. Circadian disruption links to diverse diseases, emphasizing the urgency to comprehend underlying mechanisms. This review explores the communication between the environment and chromatin, focusing on histone posttranslational modifications. Special attention is given to the significance of histone methylation in circadian rhythms and metabolic control, highlighting its potential role as a crucial link between metabolism and circadian rhythms. Understanding these molecular intricacies holds promise for preventing and treating complex diseases associated with circadian disruption.